2018
DOI: 10.5194/hess-22-4229-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modelling biocide and herbicide concentrations in catchments of the Rhine basin

Abstract: Abstract. Impairment of water quality by organic micropollutants such as pesticides, pharmaceuticals or household chemicals is a problem in many catchments worldwide. These chemicals originate from different urban and agricultural usages and are transferred to surface waters from point or diffuse sources by a number of transport pathways. The quantification of this form of pollution in streams is challenging and especially demanding for diffuse pollution due to the high spatio-temporal concentration dynamics, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…For conservative APIs we found that the emissions calculated from consumption data from Moser et al (2018) and the consumer excretion rates plus WWTP removal rates from Singer et al (2016) nicely matched the observed flux data of Ruff et al (2015) for almost each measurement point. This fact makes the same likely for the degrading compounds, thereby indirectly supporting our statements on the extent and place of degradation.…”
Section: 1029/2018wr023592mentioning
confidence: 55%
See 1 more Smart Citation
“…For conservative APIs we found that the emissions calculated from consumption data from Moser et al (2018) and the consumer excretion rates plus WWTP removal rates from Singer et al (2016) nicely matched the observed flux data of Ruff et al (2015) for almost each measurement point. This fact makes the same likely for the degrading compounds, thereby indirectly supporting our statements on the extent and place of degradation.…”
Section: 1029/2018wr023592mentioning
confidence: 55%
“…The stream network is built up from reaches, and basic physical properties were assigned based on the CCM2 river and catchment database (EU JRC, http://ccm.jrc.ec.europa.eu/). The model is calibrated for seven active pharmaceutical ingredients (APIs) using emission data from the CrossWater project (Ingold et al, 2018;Moser et al, 2018), estimated excretion and wastewater treatment plant (WWTP) removal data from Singer et al (2016), and pharmaceutical flux measurements by Ruff et al (2015). Model results are analyzed both in terms of parameter values and spatial distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Modelling expected concentrations of herbicides in catchments can provide essential insights into the exposure of aquatic primary producers to herbicides. Moser et al (2018) showed that key drivers and processes are reasonably well approximated by a simple model that includes land use as a proxy for herbicide use, weather data for the timing of herbicide applications and discharge or precipitation as drivers for transport. They could predict the timing and level of peak concentrations within a factor of 2 to 3 in a spatially distributed manner at the scale of large river basins.…”
Section: Concentrations Of Herbicides In the Aquatic Environmentmentioning
confidence: 99%
“…Herbicides originate from different urban and agricultural usages and are transferred to surface waters from point and diffuse sources by several transport pathways (Moser et al 2018). Exposure of aquatic primary producers to herbicides can occur through water for all algae and aquatic plants, through air for emergent and floating plants and through sediment for rooting plants and benthic algae ( Fig.…”
Section: Exposure Of Aquatic Primary Producers To Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation